Formation of legal knowledge in pre-school children - Tatarintseva, Nina E.; MаsеsjansElena P. (Opción, 2019)
The present study aims to develop techniques to form notions about human rights in pre-school children via qualitative research techniques such as intensive individual interviews. We found that few children knew their rights and had knowledge of inaccurate content. When the Rights and Duties program was developed, the number of children with a high level of knowledge of human rights increased drastically. In conclusion, the process of shaping legal notions has to begin at the senior pre-school age.This process will be effective if the objective-spatial environment of an educational establishment is organized in the right way